Genetic signatures of a recent anthropogenic regression in an avian top predator during the last century: bottlenecks and expansions of the Eagle Owl (Bubo bubo) in Iberian Peninsula - Graciá, Eva; Ortego, Joaquín; Blanco, Guillermo; Delgado, María del Mar; Penteriani, Vincenzo; Godoy, José A. (2014)
Resumen del trabajo presentado al 10th Ecology & Behaviour meeting, celebrado en Montpellier (Francia) del 12 al 16 de mayo de 2014.-- et al. Loss of genetic variation may affect the population ability of species to deal with rapid environmental changes or selection pressures. In this work we explore the genetic consequences of the recent bottleneck and posterior recovery of the Eurasian Eagle Owl (*Bubo bubo*) in the Iberian Peninsula. During the last century, the species suffered a sharp decline by the direct persecution of hunters and the mortality by electrocution in power lines. The legal protection of raptors since the 1970s and the correction of power lines since the 1990s, allowed for the recovery of the populations of this owl. However, it remains unknown if these population contractions and expansions could have influenced the current species' pattern of genetic diversity. We genotyped 235 eagle owl from ten subpopulations in the Iberian Peninsula using eight microsatellite markers. Genetic data revealed the existence of three genetic clusters grouping separately central, south-western and south-eastern samples. We found moderate levels of differentiation among subpopulations, following a pattern of isolation by distance. Moreover, significant signatures of recent bottleneck events were detected for the three analysed clusters. Both results show that the genetic signatures might reflect recent demographic changes in spite of the relatively high dispersal rates of the owls. Peer Reviewed